Ischemic acute tubular necrosis models and drug discovery: a focus on cellular inflammation - Ikeda, Masahiro; Prachasilchai, Worapat; Burne-Taney, Melissa J.; Rabb, Hamid; Yokota-Ikeda, Naoko (Drug discovery today, 2006)
Acute renal failure (ARF) is a common cause of mortality and morbidity in hospitalized patients. Ischemia is an important cause of ARF, and ARF caused by ischemic injury is referred to as ischemic acute tubular necrosis (ATN). There is growing evidence from models that ischemic ATN is associated with intrarenal inflammation. Consequently, intrarenal inflammation is an attractive target for the development of novel drug therapies for ARF. This review outlines ischemic ATN models, the pathophysiogical roles of inflammatory cells such as T and B cells in ischemic ATN models, and effective T and B cell therapeutic reagents.